Association of Low Vitamin D Level Status and Risk of Pre-Eclampsia and Preterm Birth in Women Using Low-Dose Aspirin - Urooj Hina; Abeera Choudry; Saira Saeed; Faiza Khanam; Uzma Urooj (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association between low Vitamin-D status and risk of pre-eclampsia and preterm birth in women using low-dose Aspirin in the tertiary care setting.